Poikiloderma With Neutropenia and Mastocytosis: A Case Report and a Review of Dermatological Signs - Piccolo, Vincenzo; Russo, Teresa; Di Pinto, Daniela; Pota, Elvira; Di Martino, Martina; Piluso, Giulio; Ronchi, Andrea; Argenziano, Giuseppe; Di Brizzi, Eugenia Veronica; Santoro, Claudia (Frontiers in Medicine, 2021)
Poikiloderma with neutropenia (PN) is a very rare genetic disorder mainly characterized by poikiloderma and congenital neutropenia, which explains the recurrence of respiratory infections and risk of developing bronchiectasis. Patients are also prone to develop hematological and skin cancers. Here, we present the case of a patient, the only child of apparently unrelated Serbian parents, affected by PN resulting from the homozygous mutation NM_024598.3:c.243G>A (p.Trp81Ter) of USB1; early onset of poikiloderma (1 year of age) was associated with cutaneous mastocytosis. We also provide a review of the literature on this uncommon condition with a focus on dermatological findings.